Evaluation of radiographic findings in chronic low back pain - M Roohi M, M, A, N,R (Babol University of Medical Sciences, 2004)
Background and Objective: Low back pain is one of the problems that involve many of people during their life, especially in old ages. It is estimated 80% of individuals experience low back pain. According to high prevalence of this problem, it is necessary to evaluate its epidemiologic characteristics. The aim of this study was to evaluate the radiographic findings in chronic low back pain. Methods: This study was performed on 547 patients with chronic low back pain referred to Yahyanejad hospital in 2001. Plain anterior-posterior radiographies were taken and if there was any doubt about spondylolysis, right and left oblique radiographies were requested. All findings were detected from these graphs. Findings: 408 women (74.6%) and 139 men (25.4%) were participated in this study. In 286 of cases, there was not any radiologic finding. The most frequent radiographic findings were: Spondylolysis (21.6%), narrowing L4-L5 (7.9%). There was a significant relation between spondylolisthesis, narrowing >L4, flat back and narrowing L4-L5 and age (P<0.05). Also spondylolisthesis L4-L5 and narrowing L5-S1 were more frequent in female (P=0.005 and P=0.041, respectively). Conclusion: More than half of patients have positive radiographic findings. So, it is advisable to take lumbosacral radiography before any treatment of chronic low back pain.